Utilization of very low density lipoprotein by rat heart: the effect of endotoxin. - Bennett, M; Hauton, D; Hole, D; Evans, R (2000)
The effect of endotoxin on myocardial utilization of very low density lipoprotein (VLDL) triacylglycerol (TAG) was studied. VLDL was prepared by rat liver perfusion and tested as substrate in the isolated working rat heart. Both liver and heart donor rats were pretreated in vivo with endotoxin or vehicle (control). VLDL-TAG synthesized by endotoxin-pretreated livers was assimilated and oxidized at an increased rate by hearts compared with control VLDL-TAG, regardless of the cardiac endotoxic status, with increased cardiac mechanical performance (cardiac output, hydraulic work). There was no change in incorporation of labeled VLDL lipids into myocardial tissue lipids. Lipoprotein lipase (LPL) activity was increased in endotoxin-pretreated hearts, and after perfusion with "endotoxic" VLDL, there was a tendency for translocation of LPL from tissue-residual to heparin-releasable compartments, but these changes were modest. Analysis of the VLDL composition showed that endotoxin-pretreated livers produced apolipoprotein (apo)-B48 VLDL with decreased particle size (and hence TAG content), but apo-B100 VLDL was unchanged. Oleate content of VLDL was increased, but there was no difference in apo-C or apo-E content. These results suggest that VLDL-TAG produced during sepsis/endotoxinemia may be destined for utilization by the heart as energy substrate. However, the mechanism for its increased efficacy is uncertain.